FANTASY AND FANTASMAGORY IN THE MODERN UKRAINIAN DRAMATURGY (CONFLICT AND CHARACTER) - Nataliya L. Yuhan (Вісник університету ім. А. Нобеля. Серія Філологічні науки)
The article analyzes the peculiarities of the conflict and the system of characters in contemporary Ukrainian plays with an “irreal” (unreal) chronotope. The works of Ukrainian playwrights from 2000 to 2010 featured a variety of conflicts embodied in them, the combination of different types of conflicts in one work, the flow of one species to another (internal – external conflicts, ideological, social, love, family, moral, religious, existential and no existences; conflicts Character – Character, Character – Group, Character – Environment, Character – Metaphysical notion). The heroes in “irreal” plays are people with extraordinary abilities, bioroboty, fantastic creatures, angels and characters from the other world. Characters are revealed in actions, dialogues and small monologues. In plays by S. Shchuchenko, interpersonal, love conflicts are the main ones. The author shows the type of hero who has killed himself in extreme abilities and kills them in all people who are not like him (“Return”); he persuades readers and viewers that harmony prevails in the world, and all people, animals and plants are connected with each other – so that the world needs to be grateful and positive (“HELP”); The playwright develops the theme of harmonious relationships between men and women (F.ART, Relic). In the works of S. Shchuchenko “Without a Horse”, J. Bezpyatchuk “The Court”, “Truba” and A. Naumov “Forward in the Promised” illustrate the conflicts between man and society. Moral conflicts become the main in the plays of N.L. Miroshnichenko “The Agreement with the Angel” (search for the main character of the meaning of his life), O. Goncharov “Seven Steps to Calvary” (creation of a vivid image of the thief-anti-Messiah Messiah-Japheth), O. Mykolaychuk-Nizovtsya “Take away the waiter from heaven, or Why do we get last year’s snow” (the creation of the static character of the hero – “antimitstsa”). In a psychological play with elements of the symbolism P. Arie “Colors” personified different age periods of Mary’s life in such characters as Woman in Pink, Woman in Orange, Woman in Red, Woman in Purple, and Woman in Black (White). The conflict of this work is exalted, it is closely connected with the main existential conflicts of mankind. In the fabulous plays of S. Shchuchenko, “Snow Queen” and V. Kovalenko, “Mirror” the world of fantastic creatures and common things is projected into problems of human relationships (interpersonal and interpersonal). The conflict of V. Kovalenko’s fairy tales can be considered internal: the results of internal conflicts that occur in the “souls” or “thoughts” of human things, affect the real reality and can change the thoughts and feelings of their masters.